Synthesis of Glycerol Carbonate and Kinetic Modeling Using ZnBr2 Catalyst - Agnes Febrianti; Sonia Sembiring; Heri Rustamaji; Herti Utami (Research in Chemical Engineering, 2025)
The rapid expansion of biodiesel production in Indonesia has resulted in a surplus of glycerol as the main by-product, which has significantly decreased its market value. To increase its economic potential, glycerol can be converted into one of its value-added derivatives such as glycerol carbonate. The purpose of this study was to obtain the best conditions for the reaction and to model the reaction kinetics. The reaction was carried out using the urea carbonylation method with glycerol to produce glycerol carbonate and ammonia. The resulting samples were analyzed using iodometric titration analysis. This study focuses on the kinetic modeling of the synthesis of glycerol carbonate from glycerol and urea using ZnBr₂ as a catalyst under optimal conditions. The highest glycerol conversion was achieved at a temperature of 130°C, the addition of 5% catalyst by weight, and a reaction time of 300 minutes, resulting in a conversion rate of 52.74%. Based on the kinetic model analysis, the first-order reversible nonelementary model can be selected as the best model to describe the overall reaction kinetics. This model provides the best balance between prediction accuracy (smallest SSE value), which is 4.42×10⁻⁷, consistency with kinetic theory (k value increases with increasing temperature), which are 0.0028, 0.0038, and 0.0042 at each temperature, namely 110°C, 120°C, and 130°C, respectively. The realistic physical parameters of A and Ea values are 10.5909 s-1 and 26.1417 kJ/mol.